FITOPARASITA DA â€œEUGENIA JAMBOS L.â€: â€œPUCCINIA PSIDIIâ€ (WINT. 1884) - Schouten, Guilhermo B. (REVISTA DE AGRICULTURA, 2016)
FITOPARASITA DA â€œEUGENIA JAMBOS L.â€: â€œPUCCINIA PSIDIIâ€ (WINT. 1884)